TINJAUAN HUKUM BAGI PELAKU PERJUDIAN PERSPEKTIF FILSAFAT HUKUM DAN FILSAFAT HUKUM ISLAM (PERBANDINGAN KUHP DAN QONUN NOMOR 6 TAHUN 2014) - Vivi Ayu Saputri (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
Gambling is something that is considered taboo in various circles and causes polemics and even creates turmoil in this modern society. Both positive law and Islamic law prohibit gambling from being carried out, but there are still many people who justify any means to play gambling. In history, gambling cases are very difficult to eradicate, as if gambling had become commonplace and even become a habit for the community. In the current development of the era, gambling has become a social disease in our society, which naturally should be eradicated from social life. Many efforts have been made to deal with gambling cases such as providing sanctions for gambling actors, for example criminal sanctions and the like, but this has not deterred and gambling is still rampant in this modern society. The formulation of the problem in the discussion this time is how legal proceedings against gambling actors are handled either in accordance with the Criminal Code article 303 concerning gambling or in accordance with Qonon Number 6 of 2014.